2017
DOI: 10.23865/arctic.v8.639
|View full text |Cite
|
Sign up to set email alerts
|

Soft Law, Solid Implementation? The Influence of Precision, Monitoring and Stakeholder Involvement on Norwegian Implementation of Arctic Council Recommendations

Abstract: The Arctic Council has been criticized for its lack of legal status and, consequently, the supposedly low level of implementation among member states. Studying Norwegian implementation of six Arctic Council recommendations, this article challenges that view. I start by assuming that international law is not binary, that soft law is not a uniform phenomenon, and that soft law recommendations may entail certain characteristics*precision, monitoring, and stakeholder involvement*that can enhance their implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
1
Order By: Relevance
“…These recommendations and actions, aimed at making knowledge generation policy relevant, could be seen as a move towards the declared ambition of the AC to expand its role from policyshaping into policymaking (Arctic Council, 2013). They could also be seen as confirming the general conception that the Council is a forum for soft law (Soltvedt, 2017). However, it is noteworthy that the Council's recommendations and actions on biodiversity are generally less prescriptive and broader than in its other fields of cooperation.…”
Section: Sciencementioning
confidence: 55%
See 1 more Smart Citation
“…These recommendations and actions, aimed at making knowledge generation policy relevant, could be seen as a move towards the declared ambition of the AC to expand its role from policyshaping into policymaking (Arctic Council, 2013). They could also be seen as confirming the general conception that the Council is a forum for soft law (Soltvedt, 2017). However, it is noteworthy that the Council's recommendations and actions on biodiversity are generally less prescriptive and broader than in its other fields of cooperation.…”
Section: Sciencementioning
confidence: 55%
“…However, legal bindingness may not be a prerequisite for a stronger framework and effective implementation of commitments by Arctic states and the AC (Koivurova, Kankaanpaa, & Stępien, 2015). Legally binding instruments may have weak and poorly implementable commitments, whereas the soft law recommendations commonly adopted by the AC outside the biodiversity realm may be well suited for implementation (Smieszek, 2019;Soltvedt, 2017). Essential features of commitment as drivers of implementation are precision in formulation, monitoring of implementation andparticularly importantthat relevant stakeholders are involved.…”
Section: Pripmentioning
confidence: 99%
“…Their nonbinding character should thus not prevent us from comparing these guidelines to other, possibly more stringent regulations. Research has shown that under certain conditions soft law can be effective too (Skjaerseth et al, 2006;Soltvedt, 2017). In sum, this and other arguments justify a more thorough engagement with existing international environmental regulations of maritime industries in the Arctic.…”
Section: International Maritime Regulations In the Arcticmentioning
confidence: 97%
“…Imprecision and the absence of strong compliance systems increase their looseness even further. In particular, the lack of proper monitoring programs weakens the effectiveness of nonbinding instruments (Soltvedt, 2017). Moreover, the guidelines only contain modest requirements, especially when compared to other sea regions, such as the northeast Atlantic.…”
Section: International Organizationsmentioning
confidence: 99%
“…Klima-og miljøutfordringer i Arktis har vaert høyt på den internasjonale forskningsdagsordenen de seneste år, og kunnskap om utviklingen i nord har spilt inn i internasjonal og nasjonal politikkutforming. Dette understøttes også av enkelte juridiske og samfunnsvitenskapelige analyser, som tyder på at «arktisk kunnskap» har gjort en forskjell (se Duyck, 2012;Kankaanpää & Young, 2012;Soltvedt & Rottem, 2016;Prip, 2016;Rottem, 2017;Soltvedt, 2017;Froukje, Steindal & Borch, 2018). I denne artikkelen ser vi naermere på den viktigste kunnskapsaktøren i Arktis -Arktisk råd -som gjennom en årrekke har satt dagsordenen for kunnskapsutviklingen i nord.…”
Section: Introduksjonunclassified